Chest x-ray findings and outcomes of children with suspected ventilator-associated pneumonia - Neni Sumarni; Muhammad Sholeh Kosim; Mohammad Supriatna; Eddy Sudijanto (Paediatrica Indonesiana, 2012)
Background Ventilator-associated pneumonia (VAP) is anosocomial infection in patients who have received mechanicalventilation (MV), either by endotracheal intubation ortracheostomy, for more than 48 hours. YAP represents 80% ofall hospital-acquired pneumonias. VAP incidence varies from5.1 %-33.3%. The modified clinical pulmonary infection scoreis a criteria for diagnosing suspected YAP and typically includesradiographic evidence. YAP is associated with significantmorbidity and mortality.Objective To determine the relationship between chest x-rayfindings and outcomes in children Mth suspected VAP.Methods This retrospective study was held in Dr. Kariadi Hospitalfrom January - December 2010. Data was collected from medicalrecords of pediatric ICU (PICU) patients with suspected VAP.Chest x-ray findings and patient outcomes were recorded. X-rayfindings were assessed by the on-duty radiologist. Chi square testwas used for statistical analysis.Results Subjects were 30 children consisting of 14 males and 16females. Patient outcomes were 23 patients survived and 7 patientsdied. Chest x-ray findings were categorized into the followinggroups and compared to patient survivability: diffuse infiltrates76.7% (OR=0.694; P=0.532; 95% CI 0.102 to 4.717), localhedinfiltrates 13.3% (OR=4.200; P=0.225; 95% CI 0.470 t037.49),and no infiltrates 10% (OR=1.222; P=0.436; 95% CI 0.593 to0.926). None of the x-ray findings had a significant correlationto patient outcomes.Conclusion There was no significant relationship between chestx-ray findings and outcomes in children with suspected VAP.[Paediatr rndones. 2012;52:233-8].